Optimalisasi Kinerja Dosen Melalui Pelatihan Penulisan Ilmiah Jurnal Terakreditasi Sinta - Meliza Zafrizal (STMIK Royal, 2024)
Generating quality published articles is one of the lecturers' obligations. This can improve lecturer performance and have an impact on increasing higher education accreditation. However, there are still many lecturer articles published in uncredited journals. Apart from that, there are still many lecturers who do not understand the systematics of writing in accredited national journals. Therefore, the faculty of economics and business, Pekalongan University carries out scientific writing and publication training as well as utilizing the SINTA account to improve lecturer performance. The training was carried out in four stages, namely the initial survey stage, the training material socialization stage, the writing practice stage and utilizing the SINTA account, and the activity evaluation stage. The survey results showed that there was an increase in the percentage of participants who understood the systematics of writing in the SINTA journal from 57% before the training to 91% of the total. Meanwhile, the percentage of participants who were able to utilize the SINTA account also increased from 44% before the training was carried out to 82% after the training was carried out. Keywords: lecturer performance; reserach; article publication